Effects of deep brain stimulation on rest tremor progression in early stage Parkinson disease. (31st July 2018) - Hacker, Mallory L.; DeLong, Mahlon R.; Turchan, Maxim; Heusinkveld, Lauren E.; Ostrem, Jill L.; Molinari, Anna L.; Currie, Amanda D.; Konrad, Peter E.; Davis, Thomas L.; Phibbs, Fenna T.; Hedera, Peter; Cannard, Kevin R.; et al.
Abstract : Objective: To evaluate whether the progression of individual motor features was influenced by early deep brain stimulation (DBS), a post hoc analysis of Unified Parkinson's Disease Rating Scale–III (UPDRS-III) score (after a 7-day washout) was conducted from the 2-year DBS in early Parkinson disease (PD) pilot trial dataset. Methods: The prospective pilot trial enrolled patients with PD aged 50–75 years, treated with PD medications for 6 months–4 years, and no history of dyskinesia or other motor fluctuations, who were randomized to receive optimal drug therapy (ODT) or DBS plus ODT (DBS + ODT). At baseline and 6, 12, 18, and 24 months, all patients stopped all PD therapy for 1 week (medication and stimulation, if applicable). UPDRS-III "off" item scores were compared between the ODT and DBS + ODT groups (n = 28); items with significant between-group differences were analyzed further. Results: UPDRS-III "off" rest tremor score change from baseline to 24 months was worse in patients receiving ODT vs DBS + ODT ( p = 0.002). Rest tremor slopes from baseline to 24 months favored DBS + ODT both "off" and "on" therapy ( p < 0.001, p = 0.003, respectively). More ODT patients developed new rest tremor in previously unaffected limbs than those receiving DBS + ODT ( p = 0.001). Conclusions: These results suggest the possibility that DBS in early PD may slow rest tremor progression. Future investigation in a larger cohort is needed, and these findings will be tested in the Food and Drug Administration–approved, phase III, pivotal, multicenter clinical trial evaluating DBS in early PD. Classification of evidence: This study provides Class II evidence that for patients with early PD, DBS may slow the progression of rest tremor.